Gen Y in workplace: An exploratory study - Romiza Md Akhir; Noor Raihan AB Hamid (Proceedings of AICS - Social Sciences, 2017)
The increasing number of Gen Y entering the workforce has urged organizations to change their views on workplace effectiveness. This is because Gen Y possesses certain characteristics that are different from generations before them. By understanding Gen Y’s work-related attitude and preferences, employers would be able to accommodate and implement the strategies aligned with gen Y’s strength and weaknesses. This exploratory study aimed to explore the work-related attitude of Gen Y in terms of the daily work routines and their work expectation. It is crucial for organizations to understand their preferences in developing effective ways to retain them in the organizations. Utilizing questionnaire surveys, data was collected from final year students who have undergone practical training and newly employed Gen Y in the workplace. Based on the difference characteristics posed by Gen Y compared to the previous generations, this study is aimed to compute the reliability of the scale in measuring the work-related characteristics of Gen Y.